Synthesis and characterization of Sr2+ and Gd3+ doped magnetite nanoparticles for magnetic hyperthermia and drug delivery application. Issue 12 (15th June 2023) - Olusegun, Sunday J.; Osial, Magdalena; Majkowska-Pilip, Agnieszka; Żelechowska-Matysiak, Kinga; Nieciecka, Dorota; Krajewski, Michal; Pękała, Marek; Krysinski, Pawel
Abstract: Commendable efforts have been gingered towards the fight against cancer. Nevertheless, it remains a major public health concern due to its predominant cause of death globally. Given this, we synthesized two different nanoparticles, Sr 2+ and Gd 3+ doped magnetite for magnetic hyperthermia and drug delivery application. Based on the characterization, the diffractogram shows that only one phase related to magnetite with a crystallite size of 10 nm was formed. TEM images revealed nanoparticles of spherical shapes of approximately 12 nm. There is no difference in magnetic saturation of the as-received synthesized samples (Fe3 O4 @Sr and Fe3 O4 @Gd), while the BET-specific surface area of Fe3 O4 @Gd is 8 m 2  g −1 higher than Fe3 O4 @Sr. The heat generation in alternating magnetic ﬁeld (the magnetic hyperthermia) of Fe3 O4 @Sr functionalized with citric acid and loaded with 5- fluorouracil (Fe3 O4 @Sr@CA@5-flu) is slower than Fe3 O4 @Gd@CA@5-flu. The specific absorption rate (SAR) of Fe3 O4 @Gd@CA@5-flu, 112.0 ± 10.4 W g −1 was found to be higher than that of Fe3 O4 @Sr@CA@5-flu. The thermogram shows that 11% of the drug was successfully loaded on Fe3 O4 @Gd@CA@5-flu. The release of the antitumor drug by the synthesized nanoparticle drug carriers for ovarian cancer (SKOV-3 cells) therapy showed that more than 50% of the cancer cell's viability was reduced after 72 h of incubation. The synthesized nanoparticles demonstrated a promising drug carrier for the treatment of SKOV-3 cells.